Pengembangan Sumber Daya Manusia Melalui Pendidikan Non Formal dan In Formal di Kabupaten Tuban - Adrika Fithrotul Aini (Al Hikmah: Jurnal Studi Keislaman, 2021)
This research focuses on two monotheistic texts, namely the texts named Fathul Mubin (abbreviated as FM) and Tilmisani (abbreviated as TS). This studyreveals three problems, namely the overall content of the FM and TS texts, the concept of faith in the two FM and TS texts, as well as the various attributes of Allah, and the flow of kalam adopted by the authors of the two texts. The results of this study are the content of the FM and TS manuscripts discussing in detail the concept of faith called tasdiq, taqrir, and charity. There are 20 traits that must be believed which are divided into several types, namely the nature of nafsiyah, salbiyah, ma'ani, and ma'nawiyah. Based on the whole discussion, the author concludes that the flow developed in the discussion of these two monotheistic texts is the Asy'ariyah school of thought. Keyword: Aqidah, Kalam, Nature of Allah, Asy'ariyah, Faith.